The Functions of Code-Switching in the Chinese Speech Community in Pontianak - Nikodemus Yudho Sulistyo (STBA Pontianak, 2016)
Code-switching is a sociolinguistic phenomenon commonly exists in multilingual areas. Code-switching happens when people switch from one language to another language in order to be understood by the other speaker. It has also some other functions and purposes. Pontianak, a capital city of Kalimantan Barat province in Indonesia is a multilingual speech community where people speak different languages. One of the majority communities is Chinese who speak more than one language. This paper investigates the functions of the code-switching of the Chinese communities and how does it work. The paper also tries to find out the distinct functions of the code-switching in Pontianak compared to other areas. The method used was using the interviews of open-ended questions. The result can be found that there are four functions of the code-switching in this research; justifying or reassuring function, emotional function, numbering function, and bargaining or business talk function.